PENGARUH RASIO KECUKUPAN MODAL,KREDIT BERMASALAH, EARNING, DAN LIKUIDITAS, TERHADAP PERTUMBUHAN LABA (Students' Journal of Accounting and Banking, 2013)
The present study is intended to expand the research on how Capital aspect, Non Performing Loans, Earning, and Liqidity can affect the increasing of Banking’s profit. The financial rasio used in this research was CAR,NPL,ROA,BOPO,NIM,LDR. Researcher use purposive sampling, this study find 20 sample size and those data have been meet normality and classic assumptionrest. The analysisis data use regression model, using SPSS 16 program. The results show thatmean that BOPO effect significantly negative to the increasing of banking’s profit. That means, if the ratio of BOPO goes higher, it will decrease bank’s profit.Keywords: Capital adequacy ratio, Non Performing Loan, Return On Assets, Net Interest Margin, Loan to Deposit Ratio